Non-destructive Evaluation of Integrated Piezoelectric Transducers by Thermal Waves and Thermal Pulses. (2016) - Eydam, Agnes; Suchaneck, Gunnar; Gerlach, Gerald
Abstract: In this work, we apply the thermal wave method and the thermal pulse method for non-destructive evaluation of the polarization state of piezoelectric transducers. The pyroelectric response of the transducer is analyzed after heating it by a modulated laser beam or laser pulses. We demonstrate that the Fourier transform of the pulse response of a piezoceramic plate is equal to the frequency response. The time domain signal is determined at several bandwidths of the amplifier. Frequency spectra are derived by a discrete Fourier transform and divided by the transfer function of the measurement set-up.